Antibiotic Exposure Is Not Associated With Clearance of Bronchoalveolar Growth: Results From a Prospective Ventilator-Associated Pneumonia Study. Issue 8 (August 2021) - Betzold, Richard D.; Dennis, Bradley M.; Bellister, Seth A.; Guidry, Christopher A.; Guillamondegui, Oscar D.; Drake, Wonder; May, Addison K.
Background: Ventilator-associated pneumonia is poorly understood in trauma. Ventilated trauma patients can develop bacterial burden without symptoms; the factors that influence this are unknown. Methods: Injured adults ventilated for > 2 days were enrolled. Mini-bronchoalveolar lavage was performed for 14 days or until extubation. Semi-quantitative cultures were blinded from clinicians. All cultures with > 104 colony forming units (CFU) were assessed for antibiotic exposure (ABXE) and spectrum of coverage. mBAL CFU was assessed daily. Results: 60 patients were ventilated for 9 days (median). There were 75 with > 104 CFU. 46 had > 104 CFU and no ABXE on the sample day. 74% had clearance or a decrease (CoD) in CFU without ABXE. 29 had > 104 CFU and ABXE on the sample day. 19 had ABXE with pathogen coverage. 84% had CoD in CFU. 10 had ABXE with no spectrum of coverage. 1/10 had increased CFU and the remaining 9/10 CoD in CFU. The three groups were not statistically different on chi-squared analysis. Conclusion: Clearance of pathogens on surveillance cultures was unaffected by ABXE.